Research methods in political science an introduction using MicroCase - Le Roy, Michael K. (Thomson/Wadsworth, 2006)
This workbook includes a Windows version of MicroCase ExplorIt, a user-friendly program that makes it easy to manipulate and learn from actual data without getting bogged down in complicated statistical software. Over two dozen research-quality data files are included in this package, along with fourteen exercise worksheets (one per chapter) that let you see the real impact of the concepts they study.